Why Uganda needs a Comprehensive Tea Policy and a Tea Authority - Lakuma, Corti Paul; Munyambonera, Ezra; Guloba, Madina (My University, 2014)
Investments on Ugandan smallholders and estates to improve output, productivity and quality depends on an environment that favours a broad range of interlinked policy measures. These policy measures include land reforms, tea research and extension services, marketing and promotion, and resource mobilization and utilization. The ability of Uganda to address the above enumerated policy measures is impeded by inconsistencies. The inconsistencies arise because of existence of multiple initiatives which create uncertainty among stake holders. A study by Munyambonera et. al (2014)1 using data from the International Tea Committee (2012) draws lessons for Uganda from the approach Kenya used to coordinate the multiple interventions, ministries, departments and agencies in the tea sector-a comprehensive tea policy and a tea authority.